PEMBELAJARAN ESTETIKA WACANA TUTUR UPACARA PENGANTIN JAWA - Suwarna, Suwarna (Jurnal Cakrawala Pendidikan, 2010)
Abstract The aesthetic aspect in the Javanese wedding ceremony spoken discourse is very important and even it can take the place of the semantic aspect. Speakers emphasize more on the former than on the latter. This is the uniqueness of the Javanese wedding ceremony spoken discourse. Such a phenomenon sometimes results in a controversy between practitioners in the Javanese wedding ceremony and the audience. This study on the aesthetic aspect in the Javanese wedding ceremony spoken discourse was supported by empirical and reflective data. The analysis units included sounds, words, phrases, clauses, and sentences. On the basis of the analysis, it can be concluded that (1) the aesthetic aspect of the Javanese wedding ceremony spoken discourse comprises the phraseology, figures of speech, idioms, and aesthetic diction; and ( 2)it shows a communication register. Keywords: aesthetic aspect, Javanese wedding ceremony spoken discourse, empirical and reflective data